Meta-analysis of dimension of autonomy on the psychological well-being measurement in Indonesia - Kiswantomo, Heliany; Wardani, Ria (Universitas Muhammadiyah Surakarta, 2021)
Since it was raised more than two decades ago, research on Psychological Well-Being (PWB) in Indonesia has invited many interested people to follow up. This situation is in line with the development of the overall orientation of Positive Psychology as a form of renewal from conventional psychological orientation. A large number of PWB studies carried out in Indonesia provides quite broad theoretical and practical implications. In general, the data obtained through these studies use group norms on respondents who are relatively small in size, so that their findings are not accurate in providing a description of PWB in the group of respondents studied. Among the six dimensions psychological well-being (self-acceptance, personal growth, positive relations with others, purpose in life, environmental mental mastery, and autonomy), dimensions autonomy often show findings with lower scores than other dimensions. The purpose of this study was to find a profile of the dimensions of autonomy. The research method used is a meta-analysis and confirmation analysis of approximately 100 results of existing research, with a respondent size of around 3,000 people. After getting the score standard autonomy from the meta-analysis study, it will be continued by distributing the PWB questionnaire to around 844 respondents emerging adulthood. This research moved from the basic assumption that Indonesian culture was different from a western culture where the initial research of this PWB was developed. These cultural differences will then form different behaviors in displaying dimensions autonomy in everyday life. Keywords: autonomy; meta-analysis; positive psychology; psychological well-being; emerging adulthood.